2005
DOI: 10.1021/jf049553+
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Kafirin and Zein Oligomers by Preparative Sodium Dodecyl Sulfate−Polyacrylamide Gel Electrophoresis

Abstract: Quantitative and qualitative analysis of uncooked zein and kafirin fractions were performed through sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and electrophoretic profiles. Kafirins and zeins present the same oligomer and monomer compositions with the exception of a 66 kDa oligomer that is only present in kafirins. The quantitative analysis showed differences between zein and kafirin. The composition of each oligomer was established via preparative SDS-PAGE. Part of the cooked oligome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 6 publications
5
30
0
1
Order By: Relevance
“…In industrialized nations, sorghum is mainly cultivated as animal feed and more recently as a feedstock for biofuel production. Known chemical (or physical) mechanisms that render sorghum protein resistant to enzymatic digestion include covalent cross-linking between kafirin proteins (the main sorghum storage proteins) through disulfide bonding (S-S) (Duodu et al, 2003;Nunes et al, 2005;Belton et al, 2006), and interaction of protein with cellular chemical components such as polyphenol, phytic acid, lipids, starch, and nonstarch cell wall polysaccharides (Chavan et al, 1979;Makokha et al, 2002;Duodu et al, 2003;Nunes et al, 2004;Osman, 2004;Taylor et al, 2007;Wong et al, 2009). Decades of research to improve the trait has not yet produced high-protein-digestible sorghum cultivar with acceptable agronomic characteristics.…”
Section: Genetic Basis Of Protein Digestibility In Grain Sorghummentioning
confidence: 99%
See 1 more Smart Citation
“…In industrialized nations, sorghum is mainly cultivated as animal feed and more recently as a feedstock for biofuel production. Known chemical (or physical) mechanisms that render sorghum protein resistant to enzymatic digestion include covalent cross-linking between kafirin proteins (the main sorghum storage proteins) through disulfide bonding (S-S) (Duodu et al, 2003;Nunes et al, 2005;Belton et al, 2006), and interaction of protein with cellular chemical components such as polyphenol, phytic acid, lipids, starch, and nonstarch cell wall polysaccharides (Chavan et al, 1979;Makokha et al, 2002;Duodu et al, 2003;Nunes et al, 2004;Osman, 2004;Taylor et al, 2007;Wong et al, 2009). Decades of research to improve the trait has not yet produced high-protein-digestible sorghum cultivar with acceptable agronomic characteristics.…”
Section: Genetic Basis Of Protein Digestibility In Grain Sorghummentioning
confidence: 99%
“…By comparing the protein digestibility of whole grain, isolated endosperm, and isolated protein bodies, Duodu et al (2002) showed that sorghum protein digestibility progressively increases as grain structural complexity decreases, with whole grain protein digestibility < endosperm protein digestibility < digestibility of protein body. In a mature dry grain, the amount of cross-linked kafirin ranges from 66 to 81% (Mazhar and Chandrashekar, 1993;Nunes et al, 2005), and kafirin polymerization is correlated with poor protein digestibility (Belton et al, 2006;Bean et al, 2011;da Silva et al, 2011b;Elkonin et al, 2013). The degree of disulfide cross-linking progressively increases throughout grain development (Mazhar and Chandrashekar, 1993;Oria et al, 1995a), and during wet cooking of sorghum flour Rom et al, 1992;Watterson et al, 1993;Ezeogu et al, 2008).…”
Section: Kafirin Proteins and Sorghum Protein Digestibilitymentioning
confidence: 99%
“…In solution, zeins became an extended structure. It is well known that these proteins are organized in oligomers, which are resistant to high temperatures and treatment with reducing reagents and they tend to form high molecular weight (HMW) aggregates [14].…”
Section: Introductionmentioning
confidence: 99%
“…This is typically done by extracting the proteins under reducing conditions and analyzing the extracts via SDS-PAGE or RP-HPLC. However, recently the polymeric proteins of sorghum were studied using techniques similar to those used in the study of the large gluten protein polymers found in wheat (13) and traditional SDS-PAGE (14). The polymeric proteins of maize have also been characterized using similar techniques (15).…”
Section: Introductionmentioning
confidence: 99%